Interdisciplinary dialogues on organizational paradox : learning from belief and science - Bednarek, Rebecca (Emerald Publishing Limited, 2021)
Interdisciplinary Dialogues on Organizational Paradox is an innovative two-part volume that enriches our understanding about paradox; both deepening the theory and offering greater insight to address the grand challenges we face in the world today. Authors demonstrate how paradox theory benefits from interdisciplinary theorizing by reaching out to disciplines beyond organizational theory and exploring best practice in undertaking such research. The 13 chapters in this double volume draw from four disciplinary realms: beliefs, physicality, expression, and social structure. Unique commentaries from thought leaders expand and assess the focal pieces of each volume. Part A: Learning from Belief and Science, explores the realms of beliefs - from Ubuntu, Ying-Yang, Christian and Islamic philosophies - and physicality - from quantum mechanics, technology, to ecology - with reflective commentaries from Jean M. Bartunek and Mary Frohlich, and Andrew Van de Ven.
Includes index.
Keywords: Organizational sociology.; Paradox.; Social structure.; Social Science -- General.; Sociology.; elektronické knihy; electronic books